The Influence of Family Supportive Supervisor Behavior on Employee Creativity: The Mediating Roles of Psychological Capital and Positive Emotion - Zhou, Xiaogang; Jin, Liujun; Wang, Yimeng; Liao, Wenqin; Yang, Honglei; Li, Liqing (Frontiers in Psychology, 2022)
In an increasingly complex external environment, innovation is an important way for companies to build sustainable competitiveness. This research discusses employee creativity from the perspective of Family Supportive Supervisor Behavior (FSSB) based on conservation of resource theory, social exchange theory, psychological capital theory and emotional spillover theory. Through a series of surveys of employees in different companies and jobs, we can understand the impact of family-supporting supervisors’ behavior on their creativity. Combined with the survey data, a structural equation model (SEM) is constructed to analyze the mediating effects of psychological capital and positive emotions based on the causal mediation model. The research found that the positive influence of family-supporting supervisors’ behavior on employees’ creativity has three forms. First, supervisors improve employees’ motivation and sense of efficacy by providing various support resources. Second, supervisors can generate positive spillover effects among employees by influencing employees’ psychological state. Third, supervisors stimulate the creativity of subordinates by promoting work participation and mobility. According to the research conclusions, in order to improve the employee creativity, we should provide incentives to encourage supervisors to carry out family support behaviors, identify employee characteristics to help supervisors provide personalized support, cultivate family supportive leaders, and attach importance to emotional support and play the role of psychological capital and positive emotions.